Fatal invention : how science, politics, and big business re-create race in the twenty-first century - Roberts, Dorothy E., 1956- (Tantor Audio, 2020)
An incisive, groundbreaking book that examines how a biological concept of race is a myth that promotes inequality in a supposedly "post-racial" era. Though the Human Genome Project proved that human beings are not naturally divided by race, the emerging fields of personalized medicine, reproductive technologies, genetic genealogy, and DNA databanks are attempting to resuscitate race as a biological category written in our genes. This groundbreaking book by legal scholar and social critic Dorothy Roberts examines how the myth of race as a biological concept-revived by purportedly cutting-edge science, race-specific drugs, genetic testing, and DNA databases-continues to undermine a just society and promote inequality in a supposedly "post-racial" era.